Hedgehog and Resident Vascular Stem Cell Fate - Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Eimear Kennedy; Dermot Walls; David Morrow; Eileen M. Redmond; Paul A. Cahill (Hindawi Limited, 2015)
The Hedgehog pathway is a pivotal morphogenic driver during embryonic development and a key regulator of adult stem cell self-renewal. The discovery of resident multipotent vascular stem cells and adventitial progenitors within the vessel wall has transformed our understanding of the origin of medial and neointimal vascular smooth muscle cells (SMCs) during vessel repair in response to injury, lesion formation, and overall disease progression. This review highlights the importance of components of the Hh and Notch signalling pathways within the medial and adventitial regions of adult vessels, their recapitulation following vascular injury and disease progression, and their putative role in the maintenance and differentiation of resident vascular stem cells to vascular lineages from discrete niches within the vessel wall.